Comparing the in-vitro antioxidant activities of selected Siddha herbal preparations Ammukkirai and Vellargu chooranam - Vinotha, S.; Ira, T.; Sri Ranjani, S. (My University, 2014)
Aim of this study was to compare the total phenolic, flavonoid contents and antioxidant activities of aqueous and methanol extracts of these chooranams. The total phenolic and total flavonoid contents were evaluated using the Folin-Ciocaleteu method and Aluminium chloride method respectively. Hot aqueous and methanol extracts of these chooranams were screened for their potential in-vitro antioxidant activities using tests such as DPPH activity, FRAP assay, ABTS activity with standards of trolox and iron chelating activity with control as EDTA respectively. All these analyses were carried out using High-throughput 96-well micro-plate reader.
Keywords: Ammukkirai chooranam; Comparing activity; In-vitro antioxidant; Herbal preparation,; Vellargu chooranam